2024
DOI: 10.1001/jamainternmed.2023.8184
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Segregation and Access to Live Donor Kidney Transplantation

Yiting Li,
Gayathri Menon,
Byoungjun Kim
et al.

Abstract: ImportanceIdentifying the mechanisms of structural racism, such as racial and ethnic segregation, is a crucial first step in addressing the persistent disparities in access to live donor kidney transplantation (LDKT).ObjectiveTo assess whether segregation at the candidate’s residential neighborhood and transplant center neighborhood is associated with access to LDKT.Design, Setting, and ParticipantsIn this cohort study spanning January 1995 to December 2021, participants included non-Hispanic Black or White ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…We assigned segregation scores for older adults with kidney failure based on the residential neighborhoods identified by their five-digit ZIP code at the time of dialysis initiation, which we used as proxies for neighborhoods. Consistent with previous research, 11,[26][27][28][29][30][31] segregation scores were categorized into tertiles: low (,7.2), medium ($7.2 and ,13.0), and high (.13.0) segregation.…”
Section: Residential Racial and Ethnic Segregation At County Levelmentioning
confidence: 73%
See 4 more Smart Citations
“…We assigned segregation scores for older adults with kidney failure based on the residential neighborhoods identified by their five-digit ZIP code at the time of dialysis initiation, which we used as proxies for neighborhoods. Consistent with previous research, 11,[26][27][28][29][30][31] segregation scores were categorized into tertiles: low (,7.2), medium ($7.2 and ,13.0), and high (.13.0) segregation.…”
Section: Residential Racial and Ethnic Segregation At County Levelmentioning
confidence: 73%
“…Segregation, rooted in historical injustices such as discriminatory zoning and redlining, 57 perpetuates unequal resource distribution and concentrated areas with poor social conditions. 25,26,57 Coupled with greater exposure to air pollution, crime, 7,58,59 and reduced social capital, these factors significantly affect the health and cognitive function of older adults with kidney failure, 14 especially within Black communities. 8 Furthermore, we found that older adults with kidney failure who relocated to neighborhoods with different segregation levels did not exhibit a significant change in their risk of dementia diagnosis compared with those who did not relocate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations